Cinobufagin inhibits tumor progression and reduces doxorubicin resistance by enhancing FOXO1-mediated transcription of FCGBP in osteosarcoma. (5th October 2022) - Ma, Xiucai; Suo, Zhigang; Ma, Xiaoyan; Zhan, Chunrui; Luo, Guodong; Song, Jianmin
Abstract: Ethnopharmacological relevance: Cinobufagin (Huachansu), an aqueous extract from the dried skin of the toad Bufo bufo gargarizans Cantor (frog skin), is a biologically active ingredient of a traditional Chinese medicine cinobufacini that can treat multiple bone pathological conditions such as bone pain, bone tumors, and osteosarcoma. Aim of the study: The study aimed to explore the roles and molecular mechanisms of cinobufagin underlying osteosarcoma development and doxorubicin (ADR) resistance. Materials and methods: Cell viability, migration, and invasion were examined by CCK-8, wound healing, and Transwell invasion assays, respectively. RNA sequencing analysis was performed in MNNG/HOS cells treated with or without cinobufagin. The relationships of cinobufagin, forkhead box O1 (FOXO1), and Fc fragment of IgG binding protein (FCGBP) were examined by luciferase reporter, immunofluorescence (IF), RT-qPCR, and chromatin immunoprecipitation (ChIP) assays together with weighted gene co-expression network analysis (WGCNA) analysis. Epithelial-mesenchymal transition (EMT) marker levels were examined through the Western blot assay. The function and molecular basis of cinobufagin in osteosarcoma were further investigated by mouse xenograft experiments. Results: Cinobufagin reduced cell viability, weakened ADR resistance, and inhibited cell migration/invasion/EMT in osteosarcoma cells. Cinobufagin enhanced FOXO1-mediated transcription of downstream genes including FCGBP. FCGBP knockdown partly abrogated the effect of cinobufagin on osteosarcoma cell development. Cinobufagin inhibited the growth of mouse osteosarcoma xenografts in vivo. Cinobufagin reduced the expression of Ki-67 and MMP9 and facilitated caspase-3 expression in osteosarcoma xenografts. Conclusion: Cinobufagin suppressed tumor progression and reduced ADR resistance by potentiating FOXO1-mediated transcription of FCGBP in osteosarcoma. Graphical abstract: Image 1 Highlights: Cinobufagin inhibited osteosarcoma cell progression and reduced ADR resistance. Cinobufagin induced the transcription of FOXO1 downstream targets. Cinobufagin enhanced the transcriptional activation of FOXO1 on FCGBP. Cinobufagin exerted its function partially by up-regulating FCGBP. Cinobufagin inhibited the growth of osteosarcoma xenografts.